The role of dietary methionine concentrations on growth, metabolism and N-retention in cobia (Rachycentron canadum) at elevated water temperatures - Nguyen, Minh Van (2019)
This study determined impacts of dietary methionine concentrations at two temperatures on growth, feeding efficiency and N-metabolites in juvenile cobia. Methionine concentrations of the experimental diets were deficient (M9; 9 g/kg), sufficient (M12; 12 g/kg) and surplus (M16, 16 g/kg). Water temperature was normal (30°C) or elevated (34°C). Twenty cobia in triplicate tanks were fed the experimental diets for 6 weeks. Both methionine and temperature affected cobia's growth and feeding efficiency. Cobia fed M9 performed lower than the fish fed M12 and M16 diets. Additionally, cobia reared at 34°C performed poorer than at 30°C, probably due to lower voluntary feed intake in the fish reared at 34°C. Protein efficiency ratio and protein productive value in cobia fed M9 diet were less than M12 or M16 diets. This was confirmed with the improved retentions of indispensable amino acids (AAs). No interactions between methionine and temperature were observed in growth and protein accretion. At 30°C, CF improved, while HSI and VSI declined upon methionine supplementation levels. Of which an interaction between temperature and methionine was present. Plasma, muscle and liver free AA and N-metabolites were affected by methionine and temperature. Furthermore, temperature affected cobia's lipid class composition, resulting in increased phospholipids and cholesterol at 34°C.